PENGARUH KUALITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, DAN SISTEM PENGENDALIAN INTERN TERHADAP KEANDALAN PELAPORAN KEUANGAN PEMERINTAHAN DESA DI KABUPATEN KLATEN - Dewi Kusuma Wardani; Ika Andriyani (Jurnal Akuntansi, 2017)
The purpose of this study to examine the effect implementation of the influence of human resource quality, exploiting of information technology, and internal control system for reliability of the Government Financial Reporting Countability village in Klaten district. This research is causative research. The population in this study is the village in Klaten district government, especially government Manisrenggo village in the district and every village government was represented by seven people that the village head and village as respondents. Data collection is done directly by using a questionnaire. While the tools of analysis used was multiple regression with SPSS program version 16.0. The results show that the variable human resource quality and internal control system have influence to reliability of financial reporting in the Klaten district of the village administration, while exploiting of information technology has no influence to reliability of financial reporting in the Klaten district of the village administration Keywords: Reliability of Financial Reporting, Human Resource Quality, Exploiting of Information Technology, and Internal Control System